Gastric Cancer With Peritoneal Metastasis—A Comprehensive Review of Current Intraperitoneal Treatment Modalities - Prabhu, Aruna; Mishra, Deepti; Brandl, Andreas; Yonemura, Yutaka (Frontiers in Oncology, 2022)
The treatment of patients with peritoneal metastasis from gastric cancer continues to evolve. With various forms of intraperitoneal drug delivery available, it is now possible to reach the sites of peritoneal metastases, which were otherwise sub-optimally covered by systemic chemotherapy owing to the blood peritoneal barrier. We conducted a narrative review based on an extensive literature research highlighting the current available intraperitoneal treatment options, which resulted in improved survival in well selected patients of peritoneally metastasized gastric cancer. Intraperitoneal chemotherapy showed promising results in four different treatment modalities: prophylactic, neoadjuvant, adjuvant, and palliative. It is now possible to choose the type of intraperitoneal treatment/s in combination with systemic treatment/s, depending on patients' general condition, peritoneal disease burden, thus providing individualised treatment to these patients. Randomised controlled trials for the different treatment modalities were mainly conducted in Asia, and lack further validation in the other parts of the world. Most recent application tools, such as pressurized intraperitoneal aerosol chemotherapy seem promising, and need to pass the ongoing clinical trials.